Acidification profile, probiotic in vitro gastrointestinal tolerance and viability in fermented milk with fruit flours - Casarotti, Sabrina Neves [UNESP]; Barretto Penna, Ana Lucia [UNESP] (Elsevier B.V., 2015)
The effect of addition of apple, banana and grape flours (1%) on the characteristics of fermented milk by culture ABT-4 was evaluated. Supplementation with fruit flour affected only the acidification rate, and there was no effect on fermentation time. There was a decrease in the pH level and an increase in titratable acidity throughout storage. The level of probiotics was not affected by milk supplementation with fruit flours during 28 days of storage. Decreased probiotic survival during in vitro gastrointestinal simulation was observed in all the treatments. Nonetheless, the supplementation with fruit flours improved Lactobacillus acidophilus tolerance to simulated gastrointestinal conditions, specifically at days 14 and 28 of storage. On the other hand, only banana flour had a protective effect on Bifidobacterium animalis subsp. lactis after 28 days of storage. This is the first report that demonstrated a protective effect of fruit flours on the simulated gastrointestinal resistance of probiotics. (C) 2014 Elsevier Ltd. All rights reserved.